Knowledge and awareness of dental stem cells among dental healthcare professionals – a cross-sectional study - Hafsa Qabool; Jaweriya Qabool; Aqeel Ahmed; Rashna Hoshang Sukhia; Mubassar Fida (Journal of the Pakistan Medical Association, 2023)
Objective: To assess knowledge and awareness of dental healthcare professionals on dental stem cells. Methods: A questionnaire survey-based study was conducted using Google forms on a sample of 69 dental healthcare professionals (DHCP) from September – October 2022, after obtaining ethical approval. A validated questionnaire was used to assess the knowledge and awareness of dental healthcare professionals on stem cells, which was then divided into three sections. The section A was about demographic statistics, section B assessed knowledge and awareness regarding dental stem cells and section C consisted of 5 score VAS scale to assess the acceptability of future research and increase implication of dental stem cells (DSC) among DHCP. The frequency of each question was reported in percentages. To assess the difference of knowledge and awareness of DSC among different specialties of DHCP, one-way ANOVA test was applied and incase of significant results pairwise comparison was performed by post-hoc Tukey test. Results: Mean scores of knowledge and awareness of DSC among female DHCP were 54.26 ± 11.73 and males were 53.50 ±8.19. There was a statistically significant difference of knowledge (p= 0.02) among different dental healthcare professionals. On pairwise comparison by post-hoc Tukey HSD we found statistically significant difference (p = 0.03) of knowledge and awareness of dental stem cells among general dentists and operative dentistry specialists. Conclusion: We found poor knowledge and awareness of dental healthcare professionals regarding dental stem cells. However, operative and endodontic specialty had more awareness on dental stem cells as compared to any other specialty. There was positive approach for further future researches on stem cells. Keywords: Dentistry, Operative, Stem Cells, Demography.